Climate drivers of Southern Ocean phytoplankton community composition and potential impacts on higher trophic levels - Krumhardt, Kristen M.; Long, Matthew C.; Sylvester, Zephyr T.; Petrik, Colleen M. (Frontiers in Marine Science, 2022)
Southern Ocean phytoplankton production supports rich Antarctic marine ecosystems comprising copepods, krill, fish, seals, penguins, and whales. Anthropogenic climate change, however, is likely to drive rearrangements in phytoplankton community composition with potential ramifications for the whole ecosystem. In general, phytoplankton communities dominated by large phytoplankton, i.e., diatoms, yield shorter, more efficient food chains than ecosystems supported by small phytoplankton. Guided by a large ensemble of Earth system model simulations run under a high emission scenario (RCP8.5), we present hypotheses for how anthropogenic climate change may drive shifts in phytoplankton community structure in two regions of the Southern Ocean: the Antarctic Circumpolar Current (ACC) region and the sea ice zone (SIZ). Though both Southern Ocean regions experience warmer ocean temperatures and increased advective iron flux under 21st century climate warming, the model simulates a proliferation of diatoms at the expense of small phytoplankton in the ACC, while the opposite patterns are evident in the SIZ. The primary drivers of simulated diatom increases in the ACC region include warming, increased iron supply, and reduced light from increased cloudiness. In contrast, simulated reductions in ice cover yield greater light penetration in the SIZ, generating a phenological advance in the bloom accompanied by a shift to more small phytoplankton that effectively consume available iron; the result is an overall increase in net primary production, but a decreasing proportion of diatoms. Changes of this nature may promote more efficient trophic energy transfer via copepods or krill in the ACC region, while ecosystem transfer efficiency in the SIZ may decline as small phytoplankton grow in dominance, possibly impacting marine food webs sustaining Antarctic marine predators. Despite the simplistic ecosystem representation in our model, our results point to a potential shift in the relative success of contrasting phytoplankton ecological strategies in different regions of the Southern Ocean, with ramifications for higher trophic levels.